High-Drain Field Impacting Channel-Length Modulation Effect for Nano-Node N-Channel FinFETs - Mu-Chun Wang; Wen-Ching Hsieh; Chii-Ruey Lin; Wei-Lun Chu; Wen-Shiang Liao; Wen-How Lan (Crystals, 2021)
Three dimensional (3-D) FinFET devices with an ultra-high Si-fin aspect ratio have been developed after integrating a 14Å nitrided gate oxide upon the silicon on insulator (SOI) wafers through an advanced CMOS logic platform. Under the lower gate voltage (VGS-VT) and the higher drain/source voltage VDS, the channel-length modulation (CLM) effect coming from the interaction impact of vertical gate field and horizontal drain field was increased and had to be revised well as the channel length L was decreased. Compared to the 28-nm MOSFETs, the interaction effect from the previous at the tested FinFETs on SOI substrate with the short-channel length L is lower than that at the 28-nm device, which means the interaction severity of both fields for nFinFETs is mitigated, but still necessary to be concerned.